On the distribution of maximum of multivariate normal random vectors. Issue 10 (19th May 2019) - Nadarajah, Saralees; Afuecheta, Emmanuel; Chan, Stephen
Abstract: Let be a multivariate normal random vector. We derive explicit expressions for the cumulative distribution function, probability density function and the moments of . Each expression involves single infinite sums of known special functions. Computational issues like accuracy, convergence, time and simulations are investigated.